CASKIN2 mediates PTPσ-orchestrated transsynaptic mechanisms at excitatory synapses - Kyung Ah Han; Gyubin Jang; Hee-Yoon Lee; Byeongchan Kim; Tayo Kanato; Virág Vas; László Buday; Xinran Liu; Se-Young Choi; Ji Won Um; Jaewon Ko (Proceedings of the National Academy of Sciences, 2025)
Presynaptic active zones (AZs) perform essential functions in orchestrating speedy and accurate neurotransmission. Despite extensive studies on their molecular constituents, it remains unclear how transsynaptic signals are organized at AZs. The two members of the CASKIN family of multidomain scaffold proteins, CASKIN1 and CASKIN2, bind to several AZ proteins and LAR receptor protein tyrosine phosphatases (LAR-RPTPs), and thus likely contribute to presynaptic assembly. Analysis using conditional knockout (cKO) mice deficient for CASKIN1 and/or -2 revealed that CASKIN2, but not CASKIN1, is critical for proper synaptic transmission, synaptic strength, and AZ protein arrangement at glutamatergic synapses. CASKIN1/2 deletion recapitulates Caskin2 -cKO phenotypes. Strikingly, presynaptic CASKIN2 at hippocampal CA3 neurons specifically regulates postsynaptic N -methyl- D -aspartate receptor (NMDAR)-mediated responses, NMDAR surface expression, and long-term potentiation in CA1 pyramidal neurons. Moreover, PTPσ-mediated tyrosine dephosphorylation and multimerization of CASKIN2 are critical for the ability of CASKIN2 to regulate excitatory synaptic transmission, NMDAR functions, and activity-dependent presynaptic F-actin rearrangement. Last, the presence of CASKIN2 and PTPσ at Schaffer collateral circuits contributes to proper novel object location memory in mice. Our findings establish crucial roles of CASKIN2 in orchestrating LAR-RPTP-mediated transsynaptic NMDAR-related synaptic functions.